The Influence of Language on Interaction and Communication Within Social Media Platforms: - Nuryati Nani (Focus Journal : Language Review, 2024)
This study examines the influence of language on interaction and communication within social media platforms. Language, as a primary tool for conveying messages, plays a crucial role in shaping digital identities, building social relationships, and influencing how information is perceived by users. In this context, language not only serves as a medium for communication but also acts as a bridge for culture, social norms, and self-expression. The research identifies various linguistic phenomena that emerge on social media, such as the use of slang, colloquial expressions, code-switching, and their impact on effective communication. The findings suggest that language on social media tends to be more informal, flexible, and adaptive, creating space for the development of new linguistic forms and influencing communication patterns in everyday life. In conclusion, language on social media not only reflects social and cultural evolution but also plays a significant role in shaping the dynamics of digital communication in the modern era.